Owner expectations and surprises of dog ownership experiences in the United Kingdom - Anderson, Katharine L.; Holland, Katrina E.; Casey, Rachel A.; Cooper, Ben; Christley, Robert M. (Frontiers in Veterinary Science, 2024)
Although many owners are satisfied by dog ownership, high numbers of dogs are relinquished annually, with an estimated 130,000 dogs cared for each year by rescue organisations in the UK. Unrealistic ownership expectations are a potential factor in the decision to relinquish and therefore understanding what surprises owners about the realities of ownership and how this meets their expectations is vital. Using a retrospective cross-sectional cohort study design, as part of Dogs Trust's National Dog Survey 2021, owners were asked 'what has surprised you most about owning a dog?' and to classify how their experiences had compared with their expectations on a list of aspects of ownership as either more than, less than or as expected. Free text responses (n= 2,000) were analysed using reflexive thematic analysis in NVivo Pro (v.12 QSR) and a quantitative summary of classified expectations (n=354,224) was conducted in R. Many aspects of ownership were reported to be as expected, however a discrepancy between expectation and reality regarding some aspects was revealed. The cost of vet visits was greater than expected for the majority of respondents (52%), whilst other factors that often exceeded expectations included rehoming cost (33%) and amount of patience needed (25%). Damage to furniture was less than expected for many (50%) as was damage to garden (33%). From the thematic analysis, four themes were generated that reflected what surprised owners most about ownership: emotional connectedness of human-dog relationships; dog's impact on human health/wellbeing; understanding what dogs are like; and meeting the demands of ownership. Overall these results aid our understanding of dog-human interactions, highlighting the complexity of the dog-owner relationship which may come with unanticipated costs. Whilst this study's results are reassuring given many aspects of ownership were as expected, and surprises were often positive, some areas had greater impacts than expected, raising opportunities for intervention, resources or support. The aim would be to manage owners' expectations prior to acquisition or ensure these are more realistically met, reducing the likelihood of negative welfare implications for both dog and owner.